Replacement of Albumin by Preovulatory Oviductal Fluid in Swim-Up Sperm Preparation Method Modifies Boar Sperm Parameters and Improves In Vitro Penetration of Oocytes - Navarro-Serna, Sergio (Animals (Basel), 2021)
SIMPLE SUMMARY: Part of the success of assisted reproductive techniques lies in gamete manipulation before the in vitro fertilization (IVF) procedure. Current chemically defined handling media lack crucial components for embryo development that exist under in vivo conditions. Recent studies of pigs have shown that the addition of reproductive fluids during in vitro fertilization and embryo culture improves embryo quality and their epigenetic profile in vitro. Porcine oviductal fluid (pOF) has been used to supplement the handling media used for sperm selection by centrifugation. However, its effect during sperm selection by the swim-up procedure is still unknown, as is the likely beneficial effect of replacing bovine serum albumin (BSA) by pOF as a protein source in sperm preparation media. In this study, four protein combinations in the swim-up medium were tested: 1 mg/mL BSA (the regular supplementation), 1% preovulatory pOF (1% pOF), 1 mg/mL BSA plus 1% pOF; and 5 mg/mL BSA. After sperm selection, various sperm parameters were assessed, and oocytes were inseminated in vitro. Results showed that the replacement of BSA by pOF improves some sperm motion parameters and increases in vitro oocyte penetration ability, whereas the combination of BSA + pOF did not show relevant effects. High concentrations of BSA had a detrimental effect, resulting in a decrease of sperm penetration. ABSTRACT: More suitable and efficient methods to protect gametes from external harmful effects during in vitro handling can be achieved by adding preovulatory porcine oviductal fluid (pOF) to in vitro culture media. The objective of this study was to assess the swim-up procedure’s suitability as a sperm selection method using a medium supplemented with 1mg/mL BSA, 1% preovulatory pOF (v/v), 1% v/v pOF plus 1mg/mL BSA, and 5mg/mL BSA. After selection, various sperm parameters were studied, such as sperm recovery rate, sperm morphology, motility (by CASA), vitality, acrosome status and intracellular calcium (by flow cytometry) and ability to penetrate oocytes in vitro. Around 2% of sperm were recovered after swim-up, and the replacement of BSA by pOF showed a beneficial reduction of motility parameters calcium concentration, resulting in an increased penetration rate. The combination of albumin and oviductal fluid in the medium did not improve the sperm parameters results, whereas a high concentration of BSA increased sperm morphological abnormalities, motility, and acrosome damage, with a reduction of calcium concentration and penetration rate. In conclusion, the replacement of albumin by preovulatory oviductal fluid in the swim-up sperm preparation method modifies boar sperm parameters and improves the in vitro penetration of oocytes.